Terapia de Aceptación y Compromiso en Adultos con Depresión: Revisión Sistemática. - Picoita Roche, Emely Fernanda (2024)
Depression is one of the most common disorders worldwide and significantly affects people's quality of life, highlighting the need for effective therapeutic approaches. Acceptance and Commitment Therapy (ACT) is a useful method that encourages independence and personal control through the development of effective techniques that promote greater psychological flexibility, thus helping to reduce depressive symptoms. This systematic review aims to evaluate the effectiveness of ACT in adults with depression and analyze the sociodemographic characteristics of the participants in the reviewed studies. A comprehensive search was conducted in academic databases, including PubMed, Science Direct, Scielo, and Google Scholar, identifying a total of 13 studies that met the inclusion criteria. The selected studies were evaluated in terms of design, intervention and results to respond to the stated objectives. The results of this systematic review indicate that ACT is effective in reducing depressive symptoms in adults, as the majority of studies reported significant post-intervention improvements compared to control groups or alternative treatments. Regarding sociodemographic characteristics, the studies included participants of various ages, genders, educational levels, marital statuses, and occupations. However, the effectiveness of ACT did not vary significantly between the different groups, suggesting its applicability to a wide range of individuals with depression. In conclusion, this systematic review provides concrete evidence on the effectiveness of Acceptance and Commitment Therapy in the treatment of depression in adults, highlighting its applicability in diverse populations. These findings support the inclusion of ACT as a viable and effective therapeutic option in the management of depression